MEREK RINTISAN DI MATA MEDIA: Analisis Framing Pemberitaan Kompas terhadap Go-Jek dan Grab Bike di Awal Hadir - Persulessy, Stella Fellicia (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2015)
The phenomenon of online motorcycle is a new phenomenon that first occurred in Indonesia since 2015 that started since the presence of Go-Jek and GrabBike.The media framed Go-Jek and GrabBike differently. This research used Zhongdan Pan and Gerald M. Kosicki Framing Analisys as method to analyze how the news frames of Go-Jek and GrabBike formed by Kompas.com in two months of the beginning of the launch of their mobile application and what factors that influence news content of Go-Jek and GrabBike in the that two months in Kompas.com. This research concludes that in the first two months, Kompas.com equally frames Go-Jek and GrabBike in positive way, but the differences are GoJek framed as an innovation through the assessment of Jakarta government's, while GrabBike framed as the success of the motorcycle online application. The factors that influence the news content of Go-Jek and GrabBike in the first two months are the news value, market tastes or the reader's interest, and the interest of the media market